PENGARUH PROMOSI, KUALITAS PRODUK, CITRA MERK DAN HARGA TERHADAP PENGALIHAN MERK HANDPHONE YANG DIMEDIASI OLEH KEPUASAN KONSUMEN PADA MAHASISWA FAKULTAS EKONOMI DI UNIVERSITAS SYIAH KUALA BANDA ACEH - Muhammad Budiara; Muhammad Basyir (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
: This study aims to measure the effect of Influence of Promotion, Product Quality, Brand Image, and Price on Mobile Brand switching at Syiah Kuala University Faculty of Economics Students. The sample used in this study was mobile users at the Unsyiah Economics faculty totaling 246 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Non Probability Sampling. Purposive Sampling is used as an analytical method to determine the effect of all the variables involved.The results of this study indicate that promotion, product quality, brand image, and price have a significant positive effect on brand switching, and customer satisfaction, then promotion, product quality, brand image, and price have a significant positive effect on brand switching, and also the results that satisfaction Consumers mediate the relationship between promotion, product quality, brand image, price and brand switching.